The Role Of Metaphor In The Formation Of Polysemy In Uzbek And English Languages - O'ktamova, Moxigul; Mukhtorjonova, Madinaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article applies the general phenomenon of polysemy in Uzbek and English languages, paying attention to the role of metaphor in the formation of several interrelated meanings within one lexical unit. The article discusses the historical development of words with meaning expansion and the psychological impact of metaphor in the process of understanding and using language.